2012
DOI: 10.1016/j.vetimm.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

How selection for reproduction or foundation for longevity could have affected blood lymphocyte populations of rabbit does under conventional and heat stress conditions

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 (total, T CD5 + , CD4 + and CD8 + ) was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…Indeed, in livestock animals selection for fast-growing is often accompanied by a reduction in immune responses. In agreement with Ferrian et al (2012), who found a lower immune response in rabbits selected for litter size, a depressive effect of genetic selection on immunity could be hypothesised (Reid, 1995).…”
Section: Resultssupporting
confidence: 71%
“…Indeed, in livestock animals selection for fast-growing is often accompanied by a reduction in immune responses. In agreement with Ferrian et al (2012), who found a lower immune response in rabbits selected for litter size, a depressive effect of genetic selection on immunity could be hypothesised (Reid, 1995).…”
Section: Resultssupporting
confidence: 71%
“…Possible changes in resource allocation as a consequence of genetic selection or reproductive management should lead the female to situations where body condition could be withdrawn from the adequate level, increasing the susceptibility of animals to occasional immunological challenges. For example, the greatest drop in body reserves takes place at the end of gestation, which is the time of greater elimination of commercial does on the farm (Rosell and de la Fuente, 2009) and the lowest B lymphocyte counts in blood (Ferrian et al, 2012), and an excessive mobilization of the reserves at parturition conditions the success of mating during the following lactation (Quevedo, 2005;Savietto, 2013). These results would reflect the importance of not moving too far from the appropriate body status to ensure reproduction and reduce the risk of culling.…”
Section: Robustnessmentioning
confidence: 99%
“…hyper-selection concept; Cifre et al, 1998) females from commercial farms of the Iberian Peninsula having extremely long (at least 25 parturitions) and productive (minimum average litter size of 7.5 live-born kits) lives were used to establish the long-lived productive rabbit line. Since its foundation, female rabbits from long-living and productive line has been characterized by having a late reproductive senescence , a greater adaptability to maintain the productive level in the face of nutritional constrains (Theilgaard et al, 2009), a higher lymphocytes (CD14 -, CD25 + , and CD45 + ) count (Ferrian et al, 2012), and a faster immune response to a lipopolysaccharide challenge (Ferrian et al, 2013) with respect to a maternal rabbit line solely selected for litter size at weaning (Estany et al, 1989).…”
Section: Down the Rabbit Rolementioning
confidence: 99%
“…After parturition, mating was attempted on day 11, in an attempt to reach a reproductive cycle of 42 days, and only after three consecutive failures, females were culled due to performance of line V is reached at parity four; , and a better innate immune response in constrained conditions (Ferrian et al, 2012 andFerrian et al, 2013).…”
Section: Animals and Their History Of Selectionmentioning
confidence: 99%
See 1 more Smart Citation